Troponin elevation in coronary vs. non-coronary disease - Agewall, Stefan; Giannitsis, Evangelos; Jernberg, T.; Katus, Hugo (European heart journal, 2011)
Acute myocardial infarction is defined as myocardial cell death due to prolonged myocardial ischaemia. Cardiac troponins (cTn) are the most sensitive and specific biochemical markers of myocardial injury and with the new high-sensitivity troponin methods very minor damages on the heart muscle can be detected. However, elevated cTn levels indicate cardiac injury, but do not define the cause of the injury. Thus, cTn elevations are common in many disease states and do not necessarily indicate the presence of a thrombotic acute coronary syndrome (ACS). In the clinical work it may be difficult to interpret dynamic changes of troponin in conditions such as stroke, pulmonary embolism, sepsis, acute perimyocarditis, Tako-tsubo, acute heart failure, and tachycardia. There are no guidelines to treat patients with elevated cTn levels and no coronary disease. The current strategy of treatment of patients with elevated troponin and non-acute coronary syndrome involves treating the underlying causes. The aim of this paper is to review data from studies of non-ACS patients with acutely elevated troponin who in clinical practice may be difficult to discriminate from ACS patients.
online publish-ahead-of-print 18 December 2010
Gesehen am 28.02.2022